Kap Survey on The Use of Contrastors for Dental Photography by Undergraduate and Postgraduate Dental Students - Kannan, Aarthi; PM, Vikhashini (Journal of Neonatal Surgery, 2025)
Introduction: Dental photography is one of the major tools for dentistry. The first process of photography was presented to the world by Louis J. M. Daguerre at the Paris Academy of Sciences on January 7, 1839. Dental photography plays an important role for patient education, documenting cases, patient records, diagnosis and treatment planning, medicolegal purposes, and for the assessment of procedures. It's also used for training, educating, and motivating patients, for academic purposes in institutions and of late in marketing. Materials and method: A well structured questionnaire comprising 13 questions covering socio-demographic information, knowledge, attitude, perception was framed, administered and circulated to college students through an online survey link. The sample size was 100 undergraduate students and postgraduate students. Result : Among the dental students 83% of the students felt that it is important to maintain a dental photography record. 78% of the population find it time consuming, whereas the rest did not find it time consuming. Among the total participants 46% documented cases for treatment planning 34% documented cases for medical legal reasons and the rest, for better communication. 52% of the total population felt that contrastors were used to isolate the field of interest from the background, 22% of the population felt that contrastors bring out reflection of composite, 26% of the population felt that contrastors were used to stimulate darkness. Chi square value shows the p value is 0.047 (p<0.05) which is statistically significant. Conclusion: From the survey conducted among the undergraduate and postgraduate dental students, it was concluded that dental photography is a very important aspect in dentistry. Hence it is necessary to have the awareness and knowledge regarding the carius tools and techniques used to make the job easier and faster